Biological Activity of Phenolic Compounds in Extra Virgin Olive Oils through Their Phenolic Profile and Their Combination with Anticancer Drugs Observed in Human Cervical Carcinoma and Colon Adenocarcinoma Cells - Jelena Torić; Anamaria Brozovic; Mirela Baus Lončar; Cvijeta Jakobušić Brala; Ana Karković Marković; Đani Benčić; Monika Barbarić (MDPI AG, 2020)
The roles of phenolics from olive oils as effective anticancer agents have been documented in various in vitro studies of different cancer cells lines, but the relationship between the phenolic profile of olive oil and its biological activity needs more elucidation. In this study, we analysed phenolic profiles of extra virgin olive oils (EVOOs) from different autochthonous cultivars from Croatia (Oblica, Bjelica, Buža, Žižolera) and investigated the biological effect of EVOO phenolic extracts (EVOO-PEs) on human cervical (HeLa) and human colon (SW48) cancer cell lines alone and in combination with cisplatin (cDDP), carboplatin (CBP), 5-fluorouracil (5-FU) and irinotecan. The quantitative evaluation of olive oil polyphenols was performed by HPLC-DAD and spectrophotometric analysis. The biological effect of EVOO-PEs alone and in combination with anticancer drugs was measured by MTT assay. Analysed EVOO-PEs differ in phenolic profile and inhibited HeLa and SW48 cells in a dose-dependent manner. Further, it is shown that EVOO-PEs (Oblica-Sea, Buža and Žižolera), in combination with anticancer drugs, increase the metabolic activity of HeLa and SW48 cells and have a protective role. These data imply careful consummation of olive oil during chemotherapy of cancer patients.